2014
DOI: 10.1007/s00213-014-3654-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impact of social stress and coping strategy throughout development

Abstract: Rationale Stress experience during adolescence has been linked to the development of psychiatric disorders in adulthood, many of which are associated with impairments in prefrontal cortex function. Objective The current study was designed to determine the immediate and enduring effects of repeated social stress on a prefrontal cortex-dependent cognitive task. Methods Early adolescent (P28), mid-adolescent (P42), and adult (P70) rats were exposed to resident–intruder stress for 5 days and tested in an opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 65 publications
4
52
2
Order By: Relevance
“…The recognition learning and memory deficits in mixed-genotype +/− are not attributable to a lack of exposure to the objects, for time spent sniffing the two identical objects during the habituation phase was not different between genotypes or affected by social housing. A large body of literature reports impaired learning and memory in subordinate animals or animals with social stress experience during adolescence [95][96][97][98][99][100][101]. Without comprehensive data on social interactions in the home cages, or direct measurements of stress, the speculation that object recognition deficits in +/− are relevant to their subordinate status in the home cages remains to be tested.…”
Section: Discussionmentioning
confidence: 95%
“…The recognition learning and memory deficits in mixed-genotype +/− are not attributable to a lack of exposure to the objects, for time spent sniffing the two identical objects during the habituation phase was not different between genotypes or affected by social housing. A large body of literature reports impaired learning and memory in subordinate animals or animals with social stress experience during adolescence [95][96][97][98][99][100][101]. Without comprehensive data on social interactions in the home cages, or direct measurements of stress, the speculation that object recognition deficits in +/− are relevant to their subordinate status in the home cages remains to be tested.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, even though coping strategies have been positively related to WM (i.e. Putman & Roelofs, 2011;Snyder, Barry, & Valentino, 2014), sex differences in coping strategies have been widely observed. Indeed, several studies have observed that women suffer more stress than men, and their coping style is more emotion-focused than that of men (Pilar, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Putman & Roelofs, 2011;Snyder, Barry, & Valentino, 2014). Oxytocin has been related to a higher self-concept of one's own competences in both sexes (Cardoso, Linnen, Joober, & Ellenbogen, 2011).…”
mentioning
confidence: 99%
“…Training and testing of the OSST was identical to that previously described (Snyder et al, 2014) and modified from the original procedure described by Floresco et al (2008); see Supplementary Information for details. Rats were first trained to press one of two levers for food reinforcement on the first training day and the opposite lever on the following day.…”
Section: Operant Training and Testingmentioning
confidence: 99%
“…Omitted trials were not included in the TTC measure. Error types within both the SR and LD stages of the OSST were characterized using logistic regression to determine whether treatments impacted perseveration of the previous rule or the acquisition and maintenance of the new rule (see Supplementary Information; Snyder et al, 2014).…”
Section: Operant Training and Testingmentioning
confidence: 99%